Superparamagnetic iron oxide based MRI contrast agents: Current status of clinical application - Wang, Yi-Xiang J (Quantitative imaging in medicine and surgery, 2011)
Superparamagnetic iron oxide (SPIO) MR contrast agents are composed of nano-sized iron oxide crystals coated with dextran or carboxydextran. Two SPIO agents are clinically approved, namely: ferumoxides (Feridex in the USA, Endorem in Europe) with a particle size of 120 to 180 nm, and ferucarbotran (Resovist) with a particle size of about 60 nm. The principal effect of the SPIO particles is on T2* relaxation and thus MR imaging is usually performed using T2/T2*-weighted sequences in which the tissue signal loss is due to the susceptibility effects of the iron oxide core. Enhancement on T1-weighted images can also be seen with the smaller Resovist. Both Feridex and Resovist are approved specifically for MRI of the liver. The difference being that Resovist can be administered as a rapid bolus (and thus can be used with both dynamic and delayed imaging), whereas Feridex needs to be administered as a slow infusion and is used solely in delayed phase imaging. In the liver, these particles are sequestered by phagocytic Kupffer cells in normal reticuloendothelial system (RES), but are not retained in lesions lacking Kupffer cells. Consequently, there are significant differences in T2/T2* relaxation between normal tissue and lesions, resulting in increased lesion conspicuity and detectability. SPIO substantially increase the detectability of hepatic metastases. For focal hepatocellular lesions, SPIO-enhanced MR imaging exhibits slightly better diagnostic performance than dynamic CT. A combination of dynamic and static MR imaging technique using T1- and T2 imaging criteria appears to provide clinically more useful patterns of enhancement. Feridex and Resovist are also used for evaluating macrophage activities in some inflammatory lesions, but their clinical values remain to be further confirmed. The clinical development of Ferumoxtran (Combidex in the USA, Sinerem in Europe), designed for lymph node metastasis evaluation, is currently stopped.